The Effect of Storage Time on The Quality of Common Carp Sperm (Cyprinus carpio) Strain Punten in NaCL Solution and Coconut Water (Cocos nucifera L.) Extender - Triandari, Ade; Isna Hapsari, Ajeng Hanum; Iskandar, Rossdannisa; Warih Marhendra, Agung Pramana; Soewondo, Aris; Sri Rahayu (Universitas Brawijaya, 2024)
Cyprinus carpio is a freshwater species with high reproduction and adaptability. These factors make C. carpio being the freshwater fish that majority distributed and has high commercial value in some countries, including Indonesia. The maturation phase of male and female fish gonads does not occur simultaneously. Thus, sperm preservation could be an alternative technique to maintain the breeding process throughout the year. This research aims to determine the effect of storage time on C. carpio sperm quality strain Punten in NaCl solution-coconut water (Cocos nucifera L.). This study used common carp (C. carpio) 8 months of age with 500 g.bw-1. The C. carpio semen sample was divided into four treatment groups (0, 3, 6, and 9-hour storage time). The extender used in this research was composed of coconut water (C. nucifera L.) and NaCl solution with a ratio of 70% : 30%. The samples were stored in a refrigerator at 5oC. Fresh sperm sample was analyzed macroscopically using various parameters, such as pH, volume, color, and consistency. Meanwhile, the post-preserved sperm quality sample was analyzed microscopically (motility, viability, concentration, and abnormality). Furthermore, we also obtained the fertilization rate and hatching rate. The result showed that storage time affects the reduction of C. carpio sperm quality significantly (p<0.05). The highest sperm viability was obtained in NaCl solution-Cocos nucifera with a 3-hour storage time (78.33%±5.49). Our study found that the storage time significantly affected the sperm quality of C. carpio that was given with C. nucifera extender. Adding C. nucifera with 3,6,9 hour storage time also increases the fertilization and hatching rate compared with the group without C. nucifera. It can be shown that the addition of C. nucifera as a natural extender has the essential role of maintaining C. carpio sperm quality after a short storage period.